2021
DOI: 10.1016/j.xcrm.2021.100246
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of indolelactate and butyrate in multiple sclerosis revealed by integrated microbiome-metabolome analysis

Abstract: Summary Multiple sclerosis (MS) is an immune-mediated disease whose precise etiology is unknown. Several studies found alterations in the microbiome of individuals with MS, but the mechanism by which it may affect MS is poorly understood. Here we analyze the microbiome of 129 individuals with MS and find that they harbor distinct microbial patterns compared with controls. To study the functional consequences of these differences, we measure levels of 1,251 serum metabolites in a subgroup of subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 128 publications
2
46
2
Order By: Relevance
“…Prior studies in PwMS note divergent metabolomic profiles, which is consistent with our findings, 8 , 31 , 32 , 33 , 34 , 35 , 36 and several studies note alterations in AAA-related metabolites. 8 , 37 Intriguingly, one study also found reduced levels of ILA, which was linked with lower levels of ILA-producing bacteria in the gut microbiome in PwMS.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Prior studies in PwMS note divergent metabolomic profiles, which is consistent with our findings, 8 , 31 , 32 , 33 , 34 , 35 , 36 and several studies note alterations in AAA-related metabolites. 8 , 37 Intriguingly, one study also found reduced levels of ILA, which was linked with lower levels of ILA-producing bacteria in the gut microbiome in PwMS.…”
Section: Discussionsupporting
confidence: 92%
“… 8 , 37 Intriguingly, one study also found reduced levels of ILA, which was linked with lower levels of ILA-producing bacteria in the gut microbiome in PwMS. 36 Distinct from our findings, other metabolomics studies have noted differences in various lipid subspecies (phosphatidylcholine, short-chain fatty acids). 31 , 36 Differences between results from these studies and the results presented here may be related to differences in the analytical platform used to assess metabolomic profiles or differences in the underlying study populations.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…Several Trp-derived metabolites have been shown to regulate inflammation, with implications for autoimmune and neurodegenerative disorders [ 41 ]. One of the largest integrated metabolomics-metagenomic studies revealed that plasma indolelactate, indolepropionate, and its producing bacteria are lower in patients with MS compared with controls [ 80 ]. In the EAE mouse model, dietary Trp is required for induction of autoimmune neuroinflammation as mice fed a free-Trp diet have decreased numbers of circulating myelin oligodendrocyte glycoprotein (MOG) 35–55 reactive CD4 + T-cells—a finding that was dependent on the presence of an intact gut microbiota as antibiotics-treated mice do not exhibit the phenotype [ 89 ].…”
Section: The Microbiota Gut–brain Axis Mechanisms In Neurodegenerativ...mentioning
confidence: 99%
“…In line with this, the levels of circulating SCFAs are also lower [ 79 ]. A recent study demonstrated that individuals with MS have fewer species and lower levels of genes involved in butyrate production [ 80 ]. However, compared with healthy controls, MS patients have increased acetate levels, which correlated with greater disability and increased T helper 17 (T H 17) cells [ 81 ].…”
Section: The Microbiota Gut–brain Axis Mechanisms In Neurodegenerativ...mentioning
confidence: 99%